2013
DOI: 10.1021/om400434f
|View full text |Cite
|
Sign up to set email alerts
|

Assigning Hapticity to Cyclopentadienyl Derivatives of Antimony and Bismuth

Abstract: The chelating diamide [Me 2 Si{NAr} 2 ] 2− (Ar = 2,6-i-Pr 2 C 6 H 3 ) has been used as an ancillary ligand in antimony and bismuth chemistry. In contrast to the monomeric antimony chloride compound Sb(Me 2 Si{NAr} 2 ) Cl (1a), the bismuth derivative (1b) exists as a trimer in the solid state, linked by Bi•••(arene) π-bonding and Bi•••Cl interactions. Compounds 1a,b are used as an entry point into rare antimony and bismuth compounds incorporating Cp and Cp* ligands. Reactions of the chlorides with LiCp and KCp*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 53 publications
1
16
0
Order By: Relevance
“…Bulky N , N ′‐chelating diamido ligands have recently been used to support low‐coordinate organometallic, and cationic bismuth complexes. The disilylamidoether ligand [O(SiMe 2 NAr) 2 ] 2− (abbreviated NON Ar , Ar=2,6‐ i Pr 2 C 6 H 3 ) generates a sufficiently stable environment at bismuth to allow the first monomeric Bi II radical, .…”
Section: Figurementioning
confidence: 99%
“…Bulky N , N ′‐chelating diamido ligands have recently been used to support low‐coordinate organometallic, and cationic bismuth complexes. The disilylamidoether ligand [O(SiMe 2 NAr) 2 ] 2− (abbreviated NON Ar , Ar=2,6‐ i Pr 2 C 6 H 3 ) generates a sufficiently stable environment at bismuth to allow the first monomeric Bi II radical, .…”
Section: Figurementioning
confidence: 99%
“…Hirshfield surface (HS) analysis15 indicated that the only intermolecular contacts involving bismuth are weak Bi⋅⋅⋅H (1.3 % of HS) and Bi⋅⋅⋅π(arene)16 (1.2 % of HS) interactions (Supporting Information, Figure S2, Table S1), with the shortest interaction between Bi⋅⋅⋅C19′ at a distance of 3.715(4) Å. This contrasts with the molecular structure of Bi(Me 2 Si{NAr} 2 )Cl,17 in which Bi⋅⋅⋅Cl and Bi⋅⋅⋅π(arene) interactions generate a trimeric aggregate, leading us to conclude that the [NON Ar ] ligand provides effective steric protection of the bismuth center.…”
mentioning
confidence: 95%
“…The reaction of one equivalent of NEt 3 with 11 did not result in abstraction of HCl and formation of 9, with no reaction observed after 24 hours at 80 The 1 H NMR spectrum of 12a shows a single set of resonances for the SiMe 2 , isopropyl methyl and iso-propyl methine protons (δ H 0.13, 1.21 (br) and 3.49 (br) ppm, respectively). This contrasts with the spectra of 9, where two sets of resonances are observed for these protons, 95 and is consistent with a loss of the C S symmetry imposed by the pyramidal geometry of the bismuth in 9 and formation of a C 2h symmetric centre in 12a. The simplest interpretation of these data is formation of the two coordinate cation, with a mirror plane passing through the metallacycle, although other possible solution-state structures may also correspond to this new symmetry (see Appendix A).…”
Section: Reaction Of 11 With a Lewis Basesupporting
confidence: 68%
“…(THF) 3 as the tris-THF adduct, In contrast to the broad resonances observed for the bismuth mono-chloride 9, these signals are clearly defined at room temperature. 95 The more deshielded iso-propyl methyl protons appear as two separate doublets, consistent with restricted rotation for the aryl substituent adjacent to the bismuth centre.…”
Section: Research Outlookmentioning
confidence: 81%